Barriers to effective communication between family physicians and patients in walk-in centre setting in Dubai: a cross-sectional survey - Abdulaziz H. Albahri (BMC Health Services Research, 2018)
Abstract Background Effective communication between family physicians and their patients is crucial to improving healthcare outcomes and patients’ satisfaction. However, the barriers to effective communication have been weakly studied in the Gulf region with no reported studies in Dubai. This study aims to identify the main perceived barriers to effective communication between patients and their family physicians in Dubai from both the physicians’ and the patients’ viewpoints. Methods The study was conducted at 12 primary healthcare centres in Dubai between October 2016 – July 2017. Two self-administered questionnaires were used, one measuring the patients’ perceived frequency of encounters with barriers to communication, while the other was for the family physicians’ perceived level of risk to communication posed by the barriers. The barriers were assessed in the following four domains: personal characteristics and attitudes, organisational factors, communication of information, and linguistic and cultural factors. Results There were a total of 1122 patients and 170 family physicians, with 75% and 85% response rates, respectively. Having a time limitation was the highest ranking barrier, with 23.4% of patients encountering it half of the time-always, and 50.6% of physicians perceiving it as moderate-very high risk. This was followed by barriers in the communication of information domain, especially not checking the patient’s understanding and not educating the patient (16.0–16.9%) from the patients’ perception and presentation with multiple problems and not following with a treatment plan (51.2% and 35.9%, respectively), from the physicians’ perception. Preoccupation with medical records ranked in the second pentile for the physicians, and in the lowest pentile for the patients. Barriers related to the failure of rapport building and linguistic/cultural factors ranked in the fourth and fifth pentiles for both patients and physicians. Conclusion Time pressure is the major perceived barrier to communication between patients and family physicians. In addition, a greater focus needs to be placed on training the physicians to convey their messages to the patients clearly, checking their understanding and managing poor historians.